The Impact of Biopesticide Application on Arthropod Composition in Surjan Cropping System in Kulonprogo Regency, Special Region of Yogyakarta - Wagiyana Wagiyana; Suharto Suharto; Bakhroini Habriantono; Suhartiningsih Dwi Nurcahyanti; Rachmi Masnilah; Mohammad Nur Khozin; Gusna Merina; Farchan Mushaf Al Ramadhani; Dimas Ganda Permana Putra; Fariz Kustiawan Alfarisy (Journal of Applied Agricultural Science and Technology, 2025)
Surjan is a specific type of cropping system that is part of a local wisdom practice found in Kulonprogo Regency, Special Region of Yogyakarta. The cropping system employs a polyculture system with a raised-sunken bed configuration. In ancient times, this system was initiated as a conservation initiative in the event of drought. In the context of agroecosystems, defined as the interaction between biotic and abiotic components, arthropods serve as indicators of the biotic components of the agricultural environment. The presence of arthropods is influenced by the use of synthetic pesticides. In response to the use of synthetic pesticides, biopesticides are frequently used as a countermeasure. The present study aims to ascertain the impact of biopesticide applications on the composition of arthropods in agricultural land that utilizes surjan cropping system configuration. This study was conducted on the surjan cropping system in Kulonprogo Regency, which is predominantly characterized by the cultivation of rice and shallots. The biopesticide used in this study was a group of fungi, namely Trichoderma harzianum and Metarhizium anisopliae. These organisms function as bioprotectants and biofertilizers. The findings indicate that surjan cropping system, when accompanied by biopesticide utilization, yield a greater diversity of arthropod species in comparison to surjan cropping system that employs synthetic pesticides. In agricultural land with surjan system configuration and biopesticide applications, certain arthropods function as predators, parasitoids, and bioindicators. The most prevalent arthropod species identified is Verania sp. (Coleoptera; Coccinelidae), with a total of 68 individuals. The present study has yielded findings indicating a correlation between the application of surjan cropping system and the utilization of biopesticides in land cultivated with a specificcrops and the composition of arthropods in the environment.